Radioprotective Effects of Melatonin on Gamma Radiation- Induced Tissue Damage in Rats - Gholam Reza Bagheri; Hamid Reza Ghaffari; Majid Valizadeh; Hossein Ali Jahantigh; Marzieh Poursamimi; Hosein Shahriari; Javad Poursamimi (Fasa University of Medical Sciences, 2023)
Background & Objective: Gamma rays are widely used in medicine despite their harmful effects on health. Our study evaluated the protective effects of melatonin on kidney, heart, and liver tissues. Materials & Methods: Seventy-two adult male Wistar rats were categorized into nine groups. Groups 2 and 3 only received whole-body γ-ray irradiation (WBI) (2.0 Gy), no melatonin,  interval time (IT) 8hr and 24hr. Groups 4 and 5 received WBI (8.0 Gy, no melatonin, 8hr and 24hr). Groups 6 and 7 received melatonin at 60 minutes (min) before WBI(2.0 Gy). Groups 8 and 9 received melatonin before WBI(8.0 Gy). All the rats were sacrificed 8 or 24 h after the experiments for laboratory and histopathological analysis. Serum levels of Blood Urea Nitrogen(BUN), Creatinine (Cr), Lactate dehydrogenase (LDH), Potassium (K), Gamma-glutamyl Transferase (GGT), Serum Glutamic-Oxaloacetic Transaminase(SGOT), Serum Glutamic-Pyruvic Transaminase(SGPT), Alkaline Phosphatase(ALP), c-reactive protein(CRP), Troponine(TPO)  and histological features of liver, heart and kidney tissues were assessed. Statistical analysis was performed by One-Way ANOVA. Results: Our data did not indicate significant differences in BUN, Cr, K, and CRP between groups with or without melatonin treatment (P>0.05); but differences were significant for LDH, GGT, SGOT, SGPT, ALP, and TPO (P<0.05). The results showed that radiation-induced histopathological effects on the liver, heart, and kidneys were mitigated in the groups six to nine. Conclusion: The existence of significant differences in serum levels of LDH, GGT, SGOT, SGPT, ALP, and TPO in groups(6 to 9) and amelioration of the histopathological effects of irradiation on the liver, heart, and kidneys in the groups six to nine showed that the melatonin(100 mg/kg)  is able to protect the body in gamma-radiation(2.0 Gy and 8.0 Gy).